Developmental Research On Science Learning Based On Local Wisdom In Sumatra Island: A Systematic Literature Review - Huraiza Mahmudah; Ahmad Harjono; Naf'atuzzahrah; Nur Fadila; Febiyanti Ansumarwaty; Denune Galang Prawira (Postgraduate Program, University of Mataram, 2025)
This study aims to analyze developmental research on science learning based on local wisdom in Sumatra Island. The method employed is a Systematic Literature Review (SLR), allowing for a structured and comprehensive review of relevant articles by following pre-established steps. A total of 10 articles met the inclusion and exclusion criteria and were included in the final analysis. The findings reveal that science learning can be effectively integrated with local wisdom values, as science is closely related to the surrounding environment. Forms of local wisdom in Sumatra identified in the articles include the Musi River, regional flora and fauna, clay brick-making, local fermented food